Organizational Burden or Catalyst for Ideas? Disability as a Driver of Cognitive Flexibility and Creativity - Dwertmann, David J. G.; Boehm, Stephan A.; McAlpine, Kristie L.; Kulkarni, Mukta (Administrative Science Quarterly, 2025)
Disability is typically perceived negatively, and employees with a disability are viewed as a burden that requires accommodation. We draw from creativity theory to challenge this view and propose that disability can make workplace imperfections salient, can function as a situational cue that increases coworkers’ cognitive flexibility, and thus can be a catalyst for creativity. We apply a multi-study, multi-method approach to test these predictions. First, results from time-lagged and objective data in a sample of 7,037 employees from 425 units of a large German car manufacturer show that units with people with disabilities generate more ideas, particularly when employees engage in perspective taking. Second, an experiment with 954 employees shows that having a colleague with a disability has a positive individual-level effect on idea generation. Third, we extend these findings with a full model test in a second experiment of 1,314 employees, which shows that having a colleague with a disability (compared to not having a colleague with a disability) leads to more idea generation and higher idea novelty. Increased cognitive flexibility mediates these effects. Together, our findings contribute to the disability, diversity, and creativity literatures by integrating disability and creativity theory and showing that disability has the potential to serve as a catalyst for creativity and, ultimately, innovation.